A study on the factors that influence awareness of early financial saving of final semester students in UiTM Melaka City Campus / Muhammad Haikal Izzat Yusof and Nur Amalina Azanan - Yusof, Muhammad Haikal Izzat; Azanan, Nur Amalina (Faculty of Administrative Science and Policy Studies, 2014)
Recently, the rate of bankruptcy is increasing among young whereas the rate of saving is decreasing. This is due to the lack of awareness of saving among the young. Moreover, it is less focus by responsible parties towards the young on this matter. There are several factors that can affect the awareness of financial saving such as financial knowledge, financial behavior and influence from family environment. This study is carried out to identify the factors that influence awareness of early financial saving of final semester students in UiTM Melaka City Campus. The level of awareness can be either low or high based on their financial information and habit in their daily life. The respondents are selected from final semester students in UiTM Melaka City Campus as a sample. The reliability analysis, frequency analysis, normality analysis and Spearman’s Correlation were used to analyze the data. The correlation showed that the most significant factor that influences awareness of early financial saving is financial knowledge while the least is influence from family environment. The study also showed that there is relationship between financial knowledge, financial behavior, and influence from family environment towards awareness of early financial saving.